Realistic Mathematic Education (RME) Approach Assisted By Time Board Displays on The Mathematical Cognitive Abilities of Elementary School Students. - Hayun, Muhammad; Hutami, Yopana (IJBLE Scientific Publications Community Inc., 2024)
This research is motivated by the low ability of elementary school students in mathematics subjects, especially mathematical cognitive abilities, so an approach is needed to provide the right solution to this problem. The aim of this research is to find out how much influence the Realistic Mathematic Education (RME) approach assisted by time board teaching aids has on students' mathematical cognitive abilities. The research method used is an experimental method with a quasi experimental approach, with a pretest-posttest control group design, with comparative test analysis techniques for the experimental class and the control class. The results of this research showed that the average pretest score for mathematical cognitive abilities in the experimental class was 67.68 and the average posttest score was 90.77 and the N-Gain score was 68.34% with the effectiveness category being quite effective, while in the control class the average pretest score was 64.74 and posttest. 71.48 and an N-Gain score of 16.36% in the effectiveness category, namely not effective. Meanwhile, the results of the comparative test stated that the value of t = 11.62 with Sig. (one-sided p and two-sided p) 0.00 < 0.05 then H0 is rejected, which means that there is an influence between the Realistic Mathematic Education (RME) approach assisted by time board teaching aids on the mathematical cognitive abilities of class III students at SDN Cinere 1. By implementing the RME approach it is hoped that Students are more active and confident in expressing their opinions during discussions, exchanging ideas to understand and solve problems, so that mathematical cognitive abilities increase.